A scale for restaurant customers' healthy menu choices: individual and environmental factors. Issue 1 (11th December 2018) - Jeong, EunHa; Jang, SooCheong (Shawn); Behnke, Carl; Anderson, James; Day, Jonathon
Abstract : Purpose: The purpose of this study is to explore the dimensions of restaurant customers' engagement or disengagement with healthy eating in terms of individual and environmental factors to develop a scale. The results identified the underlying constructs of customers' individual motives for and perceived barriers to healthy eating, as well as environmental elements of restaurants that encourage or discourage healthy eating. Design/methodology/approach: To develop an appropriate set of measures to assess factors influencing customers' healthy eating behaviors at restaurants, the current study undertook the five steps of scale development suggested by Churchill (1979 ): specifying the domain of constructs, generating a pool of initial measurement items, assessing content adequacy, administering questionnaires (an online survey method) and purifying and finalizing the measurement (via exploratory factor analysis (EFA) using 410 samples and confirmatory factor analysis (CFA) using 423 samples). Findings: The results revealed ten individual factors (health, body image, weight control, feeling better, unappealing food, cost perception, lack of knowledge, state of mind (stress), lack of self-control and negative influences) and five environmental factors (healthy indications, social impact, availability of healthy menu, price policy and unhealthy indications) influencing customers' healthy eating behaviors at restaurants. Originality/value: This study developed an appropriate set of measures to assess individual and environmental factors influencing restaurant customers' healthy eating behaviors, along with identifying underlying sub-constructs. The reliability and validity of the scale and the factor structure are presented and potential applications and theoretical contributions of the scale are provided as well.